Effects of non-magnetic carbon nanotubes on the performance and stability of magnetorheological fluids containing FeCo-deposited carbon nanotubes - Cho, Sangwon; Kim, Hoyeon; Kim, Sehyun; Seo, Yongsok (Korea-Australia rheology journal, 2022)
Magnetorheological (MR) properties of the carbon nanotube (CNT)–FeCo nanocomposite particle suspension were investigated to find a high-performance MR fluid with great stability. The composites were fabricated by chemical deposition of FeCo on the surface of amine functionalized CNTs. The strong magnetic polarization of the FeCo moiety led to strong MR performance of the nanocomposite particle suspension. The MR fluid exhibits high yield stress value, 4 times greater than that of the suspension including Fe 3 O 4 -deposited CNT at a magnetic field strength of 86 kA/m. A three-dimensional network-like structure formed by the non-magnetic CNTs in the MR suspension does not contribute to the additional yield stress. The low density and the surface roughness of the CNTs resulted in far better long-term stability for the CNT–FeCo nanocomposite suspension than for the MR suspension of hierarchically structured Fe 3 O 4 suspension with a similar density. The effect of the three-dimensional network-like structures by the CNTs on the MR performance depends upon the interaction strength between the magnetic moiety on the CNTs.